MINIMASI WASTE PADA AKTIVITAS PROSES PRODUKSI DENGAN PENDEKATAN VALUE STREAM MAPPING (STUDI KASUS: UKM GARMEN X) - Kevin; Saryatmo, Mohammad Agung; Andres (Jurnal Mitra Teknik Industri, 2023)
SME Garmen X has been operating for more than 30 years by carrying out the production process from sheet fabric to finished clothes. SME X which is engaged in the garment manufacturing industry already has many loyal customers who entrust their clothing production with several types of models to SME X. Based on the results of observations and interviews conducted with owners and workers at SME X, information was obtained that the production process with the make to order system often experiences delays in the production process. Therefore, a lean manufacturing approach is needed to minimize waste and maximize production time. The application of lean manufacturing is carried out by making current value stream mapping, and identifying waste using the waste relationship matrix (WRM) and waste assessment questionnaire (WAQ). After the results are obtained, the next step is to select tools using the VALSAT method. Based on the results of the data, the 3 highest wastage scores were obtained, namely motion (19.89%), defect (19.22%), and waiting (16.89%). Furthermore, the results of the average score were multiplied by the detail mapping multiplier factor and the dominant tool was obtained, namely process activity mapping (PAM) of 542.23. Then analyze the causes of the problem using a fishbone diagram and five whys analysis. Improvements were made by implementing 5S, standard operating procedures, making machine setting instructions, and surprise inspections. The results show an increase in process cycle efficiency of 13.14%.